Advantages of Hybrid Corn Seed Production Compared to Corn Grain - Bahtiar Bahtiar; B Zanuddin; M Azrai (International Journal of Agriculture System, 2020)
Corn seed breeders are indispensable in the supply of superior hybrid corn seeds.  Its ability to produce seeds is evaluated for their superiority compared to the production of corn grain yield. A study was conducted in Jatirogo District, Tuban Regency, East Java province in July to December 2019. Involving farmers cooperator implementing hybrid corn seed production in the area of 96 ha and non cooperator farmers who produce the corn grain yield in the same location.  We observed the variables:  cost of production, yield and farmers income. Data and information were analyzed by Benefit Cost Ratio (B/C) and Marginal Benefit Cost Ratio (MBCR). The results showed that farmers who produced hybrid corn seeds of Nasa-29 variety (cooperators) were able to produce 4.6 t/ha of wet cobs with an income of IDR. 19,470,000/ha, while farmers who produced   grain corn of 7.9 t/ha with an income of IDR. 15,943,000/ha.  MBCR analysis showed that, the switching is able to added the farmer income Rp.4,100 for every use cost Rp.1,000 as long as the seed procurement policy remains unchanged and related institutions continue to provide support.